2019
DOI: 10.1097/j.pbj.0000000000000056
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection in patients with spinal cord injury after urodynamics under fosfomycin prophylaxis: a retrospective analysis

Abstract: Background: Urinary tract infection (UTI) is a common complication of spinal cord injury (SCI). Urodynamic testing is widely used for characterization of vesico-sphincteric dysfunction and for therapeutic orientation. As an invasive procedure, the risk of UTI is increased so, in some medical centers, antibiotic prophylaxis is instituted. Fosfomycin is one of the antibiotics used. Objective: The aim of this study was to evaluate the incidence of UTI after urodynamics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 288 publications
(382 reference statements)
0
1
0
Order By: Relevance
“…Because there are many SCI cases with asymptomatic pyuria and bacteriuria unrelated to UTI, clinicians often face a difficult choice on whether they should delay UDS in cases of pre-UDS pyuria or bacteriuria. In a retrospective study of 84 patients with SCI [ 13 ], 44.1% showed asymptomatic pre-UDS bacteriuria. Likewise, in our study, pre-UDS pyuria and bacteriuria were found in 209/399 (52.4%) and 257/399 (64.4%) patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Because there are many SCI cases with asymptomatic pyuria and bacteriuria unrelated to UTI, clinicians often face a difficult choice on whether they should delay UDS in cases of pre-UDS pyuria or bacteriuria. In a retrospective study of 84 patients with SCI [ 13 ], 44.1% showed asymptomatic pre-UDS bacteriuria. Likewise, in our study, pre-UDS pyuria and bacteriuria were found in 209/399 (52.4%) and 257/399 (64.4%) patients, respectively.…”
Section: Discussionmentioning
confidence: 99%